Exploring Emotional Intelligence and Leadership In Government: A Literature Review and Conceptual Analysis - Alan Rakhmat Putra; Johannes Johannes; Fatma Oktarendah (Sean Institute, 2025)
Leadership in government requires skills not only in technical and rational aspects, but also in managing complex emotional and social dynamics. Emotional intelligence is one of the key factors determining leadership effectiveness, because it plays a role in building communication, managing conflict, and strengthening employee trust and motivation. This study aims to conceptually analyze the role of emotional intelligence in shaping leadership effectiveness in government environments, by reviewing relevant empirical research. The results of the review indicate that emotional intelligence has a significant influence on employee performance, affective commitment, moral behavior, and innovation. The discussion highlights the five main dimensions of emotional intelligence: self-awareness, self-control, empathy, motivation, and social skills that contribute to ethical decision-making and the creation of a harmonious work climate. Furthermore, the integration of emotional intelligence in leadership has been shown to strengthen integrity and minimize the potential for bureaucratic conflict. In conclusion, emotional intelligence is not only a personal ability, but also a strategic competency necessary to realize government leadership that is adaptive, has integrity, and is oriented towards humanistic public service.